Assessment of In-Person and Cyber Aggression and Victimization, Substance Use, and Delinquent Behavior During Early Adolescence. (September 2020) - Farrell, Albert D.; Thompson, Erin L.; Mehari, Krista R.; Sullivan, Terri N.; Goncy, Elizabeth A.
This study evaluated the Problem Behavior Frequency Scale–Adolescent Report (PBFS-AR), a measure designed to assess adolescents' frequency of victimization, aggression, substance use, and delinquent behavior. Participants were 1, 263 students (50% female; 78% African American, 18% Latino) from three urban middle schools in the United States. Confirmatory factor analyses of competing models of the structure of the PBFS-AR supported a model that differentiated among three forms of aggression (in-person physical, in-person relational, and cyber), two forms of victimization (in-person and cyber), substance use, and delinquent behavior. This seven-factor model fit the data well and demonstrated strong measurement invariance across groups that differed on sex and grade. Support was found for concurrent validity of the PBFS-AR based on its pattern of relations with school office discipline referrals.